Faktor-Faktor Yang Mempengaruhi Kepuasan Wisatawan Yang Berkunjung Ke Daerah Wisata Kepulauan - Kalebos, Fatmawati (Universitas Sam Ratulangi, 2016)
The result of the reseach show the service quality, quality of the tourisme product, object and the natural tourist attraction is simoustenously effect to tourist satisfaction that already visited the location in Sitaro Island regency. The service quality in partially has influence totourist satisfaction in this research. The service quality is the highest variable that significantly to tourist satisfaction in this research. The quality of the tourisme product in partially has an influence to tourist satisfaction that visited Sitaro Island regency. The quality of the tourisme product is significantly effect to tourist satisfaction. The place and naturaltourist attraction partially has not significantly effect to tourist that visited the Sitaro Island Regency. This variable has not effect and has a negative relation.Keywords:The tourist satisfaction, island tour zone